SPACE SHUTTLE OBSERVATIONS OF TERRESTRIAL IMPACT STRUCTURES USING SIR-C AND X-SAR RADARS - Mchone J.F.; Greeley R.; Williams K.K.; Blumberg D.G.; Kuzmin R.O. (My University, 2002)
Ten terrestrial impact structures were imaged during two flights of the 1994 space radar laboratory (SRL) experiment. These craters include Wolf Creek, Australia; Roter Kamm, Namibia; Zhamanshin, Kazakhstan; BP and Oasis, Libya; Aorounga, Chad; Amguid, Algeria; and Spider, Connolly Basin and Henbury, Australia. SRL contained two co-registered instruments; the United States shuttle imaging radar-C (SIR-C) polarimetric radar system operating in L-band (λ = 24 cm) and C-band (λ = 5.6 cm), and the joint German/Italian synthetic aperture radar (X-SAR) operating in vertically-polarized X-band (λ = 3 cm).Comparisons show SRL images to be complementary to, or in some cases superior to, corresponding optical images for evaluating size, location, and relative age of impact features. Regardless of wavelength or polarization, craters with significant relief appear prominently on radar as a result of slope and roughness effects. In desert regions, longer wavelengths penetrate dry sand mantles to reveal hidden crater dimensions or associated buried landforms. Radar polarities and wavelengths are particularly sensitive to vegetation, surface roughness, and soil moisture or electrical properties. In the more temperate environments of Kazakhstan and Australia, SRL images show detailed stream patterns that reveal the location and structure of otherwise obscured impact features.